The influence of patient experience and patient trust on willingness to see a doctor based on SOR theory - Zixuan Zhao; Zhongzheng Zhang; Chunxiao Yang; Qiusha Li; Zhongming Chen; Wenqiang Yin (BMC Health Services Research, 2024)
Abstract Background Improving patients’ experience, enhancing patients’ trust and improving the willingness to see a doctor are the key to the real implementation of the “gatekeeper” role of residents’ health in township health centers. At present, in the field of health management, the research on the relationship between the three is relatively limited. The purpose of this study is to explore the current situation of patients’ experience, patients’ trust and willingness to see a doctor in township health centers, and further explore the relationship between the three, so as to provide a theoretical basis for improving the overall service and management quality of township health centers. Methods In this study, a cross-sectional survey was conducted in Shandong Province, China from July to October 2020. We used a structured questionnaire to collect data, which included general information, medical information, patient experience, patient trust, and willingness to see a doctor. Patient experience, patient trust, and willingness to see a doctor were evaluated using the Likert 5-point scoring method, with a maximum score of 5. The higher the score, the better the patient experience, the greater the patient trust, and the stronger the willingness to see a doctor. SPSS21.0 was used to describe the current situation, test the reliability and validity, and analyze the Pearson correlation. AMOS23.0 was used for structural equation modeling. Results The score of willingness to see a doctor was 3.84 ± 0.62. The score of patient experience was 3.81 ± 0.47, and the score of patient trust was 3.81 ± 0.60, which was a lower score compared to other studies in the same period. Both patient experience and patient trust both had a directly positive impact on the willingness to see a doctor, and the impact coefficients were 0.19 and 0.68, respectively. Patient experience has a direct positive impact on patient trust, with an impact coefficient of 0.74. Patient trust played a partial mediating role in the relationship between patient experience and willingness to see a doctor, and the impact coefficient was 0.50. Conclusions If the reform of China’s healthcare system is to realize the goal of “not leaving the countryside for minor illnesses and not leaving the county for serious illnesses” increasing the willingness of patients to see a doctor at the grass-roots level primary hospitals is key. In addition, the government should vigorously promote the construction of township health centers and stimulate the vitality of grass-roots health institutions. If primary hospitals want to “catch” the demand of patients, they must improve patient experience and enhance patient trust.